Ploughing is donkey work - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
A plough which is small and light enough to be pulled by donkeys and small oxen is now being manufactured in Zimbabwe as a result of cooperation between the Silsoe Research Institute, UK and Bulawayo Steel Products Ltd in Zimbabwe.Research carried...